Combining Intermittent Theta Burst Stimulation (iTBS) With Computerized Working Memory Training to Improve Language Abilities in Chronic Aphasia: A Pilot Case Study - Kranou-Economidou, Despina; Kambanaros, Maria (My University, 2022)
Background: Intermittent theta burst stimulation (iTBS) administered to the left dorsolateral prefrontal cortex (LDLPFC) has been shown to advance working memory (WM) abilities. At the same time, WM training is widely used to enhance learning associated with low language skills. An emerging area of research is that of applying cortical stimulation as an adjunct to behavioural therapy to improve language abilities in people with aphasia (PWA) after stroke. Aim: The aim of this study was to pilot the efficacy of the iTBS protocol, targeting the LDLPFC in combination with computerized WM training by measuring the near-transfer effects on WM and fluid intelligence (Gf) and far-transfer effects on language functioning and quality of life (QoL) in an individual with stroke-induced chronic aphasia. Methods & Procedures: The participant was a 31-year old female who presented with chronic non-fluent aphasia, following a left-hemisphere stroke involving the left frontoparietal lobes. She showed prominent anomia with frequent occurrences of word-finding difficulties. The assessment battery included a screening measure of WM, a standardized aphasia battery, a non-verbal intelligence test, spontaneous speech samples, a procedural discourse task, and a questionnaire addressing quality of life. All measures were administered once at baseline, immediately after treatment was terminated, and once during follow-up testing, at 3 months post-treatment. The treatment program included 10 consecutive daily sessions of 30-minutes computer-assisted WM training preceded by 3-minutes of iTBS. Outcomes & Results: Statistically significant improvement from baseline to post-treatment was found only for the non-verbal intelligence measure, suggesting near-transfer effects. There was no improvement on the computerized WM screening measure. Although no other measures revealed a statistically significant difference, there was a trend towards better performance on untreated items of receptive and expressive language tasks (far-transfer). Conclusions: The findings revealed a trend for improvement in receptive and expressive language abilities in one individual with chronic aphasia. The iTBS protocol in combination with computerised WM training could be a promising treatment but further studies with larger number of participants are needed to establish its effectiveness for improvement of aphasia after stroke.
Keywords: Aphasia; Cognition; Receptive and expressive language; Transcranial Magnetic Stimulation (TMS); Working memory